Ayurvedic Management of Motor Neuron Disease (International Journal of Ayurveda and Pharma Research, 2025)
Motor neuron disease (MND) is a neurodegenerative disorder characterized by the degeneration of both upper and lower motor neurons. Amyotrophic lateral sclerosis (ALS) is the most common form of MND. ALS is a severe neurodegenerative disorder with upper and lower motor neuron deficits in the limbs, affecting about 2 per 100,000 person/years. Brachial amyotrophic diplegia (BAD), a rare ALS variant, primarily presents with asymmetric lower motor neuron weakness, mostly affecting the upper extremities. A 75-year-old male patient diagnosed as motor neuron disease was admitted to Sri Sri College of Ayurvedic Science and Research in Bengaluru, Karnataka, on April 22, 2023 for 12 days, presenting with complaints of weakness and heaviness of both upper limbs associated with muscle wasting predominantly on right shoulder and wrist for 1 year. The clinical and laboratory features suggested a diagnosis of brachial amyotrophy diplegia, a regional variant of ALS. According to Ayurveda, Avarana vatavyadhis are found to have close resemblance to Motor Neuron Diseases and his symptoms can be correlated to Kaphavruta Vyanavata. The patient received Avaranagna and Vata vyadhi chikitsa. Assessment was done before and after treatment by using the ALSFRS-R. A satisfactory improvement was observed in the clinical findings as well as marked reduction was noted in the assessment scale. This case study suggests that brachial amyotrophic diplegia can be effectively managed symptomatically with Ayurvedic therapy.